Submerged Vacuum Membrane Distillation (S-Vmd) For Marine Aquaculture Water Desalination - Chang, Ying Shi (2021)
Vacuum membrane distillation (VMD) has been recognized as a promising desalination technology to harvest freshwater. The deaerated pores of membrane by means of vacuum in conventional VMD system tend to promote higher driving force in achieving excellent permeate flux. In a conventional VMD system, external heat supply could result in greater heat loss. Therefore, a batch submerged VMD (S-VMD) with internal heat supply was introduced in this work. The small-scale S-VMD system is beneficial to supply freshwater to the community of space-limited marine aquaculture farm in Malaysia. Inorganic compounds and nuisance microalgae in marine aquaculture water caused noticeable membrane fouling. In a preliminary study, magnesium-based crystals were dominantly fouled on the membrane at feed temperature beyond 333 K. Organic matter which is extracellular polymeric substance (EPS) that secreted by the marine microalgae was also found on the membrane surface. To evaluate the feasibility of separation and energetic performance of the S-VMD system for desalination, the system performance had been theoretically simulated and validated well with the experimental results using various operational parameters. SVMD could serve as an alternative to conventional VMD as the flux and gained output ratio (GOR) values are comparable with literatures. To achieve the baseline of theoretical flux and GOR as simulated in the numerical study, air bubbling was employed in the feed to mitigate the inorganic and organic fouling. Continuous air bubbling at a flow rate of 30 L/min provides effective surface scour to minimize inorganic crystals and EPS deposition on the membrane surface. Continuous bubbling at 30 L/min showed better cleaning efficiency and had almost constant specific energy consumption (SEC) over long-term operation. In the long-term operation over 336 h using marine aquaculture water as feed, no apparent membrane wetting was occurred with high salt rejection above 99%. The permeate met the quality standard of raw water. The obtained GOR of the air bubbling enhanced S-VMD system was 0.23, mainly contributed by stable flux and better cleaning efficiency attained. Anticipatedly, the S-VMD system can be applied in the marine aquaculture farm to produce freshwater for the fisheries community.